Windows XP Annoyances for Geeks : Tips, Secrets and Solutions. - Karp, David (O'Reilly Media, Inc., 2009)
Offering dozens of on-target tips, workarounds, and warnings, Windows XP Annoyances for Geeks allows users to improve their overall experience with the popular XP operating system. And now, with this updated edition, users can also expect detailed coverage of the newly released Service Pack 2 (SP2) technology, which provides protection against viruses, hackers, and worms. It's the ultimate resource for the ever-expanding Windows XP market.